P137 Intraductal fully covered self-expanding metal stents in biliary strictures: a UK multicentre experience. (19th June 2022) - Ahmed, Wafaa; Kyle, Dave; Khanna, Amardeep; Devlin, John; Reffitt, David; Zeino, Zeino; Webster, George; Phillpotts, Simon; Gordon, Robert; Corbett, Gareth; Gelson, William; Nayar, Manu; et al.
Abstract : Introduction: Fully covered intraductal self-expanding metal stents (IDSEMS) have been well described in the management of post-liver transplant anastomotic strictures (AS). They are increasingly used in a non-transplant (NT) setting. We conducted a multi-centre study across nine tertiary centres in the UK to analyse their use and efficacy Methods: Consecutive patients who underwent Endoscopic Retrograde Cholangiopancreatography (ERCP) with insertion of IDSEMS were retrospectively analysed. Results: 178 episodes (109 males, 61%) were identified. 162 (91%) underwent IDSEMS stent insertion for AS and 16 (9%) for a NT indication. Age at transplant was 54 years (range 12-74) and stent duration was 15 weeks (range three days-78 weeks). 131 (81%) had complete resolution of stricture at endoscopic re-evaluation. Stricture recurrence was observed in 13 (10%) cases. The most frequent indication for stenting in the NT setting was bile leak post partial hepatectomy (n=8, 50%). In the NT cohort, stent duration was 15 weeks (range 2- 41 weeks). 10 (83%) patients had complete resolution of biliary pathology on stent removal. At removal, there were 26 (14%) adverse events, five (3%) episodes of cholangitis and two (1%) of pancreatitis. In 13 (7%) cases the removal wires unravelled, 3 (2%) stents migrated, and three (2%) stents were embedded. All were removed endoscopically. Conclusions: IDSEMS appear to be safe and highly efficacious in the management of post-liver transplant AS, with low rates of AS recurrence. IDSEMS can be effectively used in the non-transplant setting.